2004
DOI: 10.2486/indhealth.42.315
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Array Analysis of Gene Expression Profiles in Brain of Mice Exposed to Manganese

Abstract: This study is performed to detect changes of gene expression in substantia nigra (SN) and striatum in manganese (Mn)-exposed mice brain. The cDNA array is a recently developed molecular biological method that can detect the differential expression of several hundreds of genes simultaneously and is therefore advantageous in the study of trace metal intoxication effect at the genetic level. Using this technology, we discovered 5 genes in the mouse striatum and 9 genes in SN changed by more than 50% following Mn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…However, excessive Mn is also toxic to the brain and can produce an irreversible syndrome resembling Parkinson's disease (Donaldson 1987;Baek et al 2003Baek et al , 2004Olanow 2006). This neurologic syndrome, known as "manganism" (Latchoumycandane et al 2005;Wasserman et al 2006) is thus characterized by a Parkinson-like condition with weakness, anorexia, apathy, slowed speech, emotionless facial expression, and slow movement of the limbs.…”
Section: Inorganic Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, excessive Mn is also toxic to the brain and can produce an irreversible syndrome resembling Parkinson's disease (Donaldson 1987;Baek et al 2003Baek et al , 2004Olanow 2006). This neurologic syndrome, known as "manganism" (Latchoumycandane et al 2005;Wasserman et al 2006) is thus characterized by a Parkinson-like condition with weakness, anorexia, apathy, slowed speech, emotionless facial expression, and slow movement of the limbs.…”
Section: Inorganic Nutrientsmentioning
confidence: 99%
“…Mn is an essential element for metalloproteins, such as glutamate synthetase, mitochondrial superoxide dismutase (Prohaska 1987;Baek et al 2004). However, excessive Mn is also toxic to the brain and can produce an irreversible syndrome resembling Parkinson's disease (Donaldson 1987;Baek et al 2003Baek et al , 2004Olanow 2006).…”
Section: Inorganic Nutrientsmentioning
confidence: 99%
“…In a genome-wide study on cultured human astrocytes (Sengupta et al 2007), Mn-induced expression changes were noted in genes involved in inflammation (upregulated), DNA replication, and repair (downregulated). Gene expression on Mn-treated mice brains (Baek et al 2004) mainly showed an upregulation of the S100β gene, and the increase of the protein was confirmed by immunohistochemistry. Instead, neurofilament subunit genes were downregulated in the striatum and in the substantia nigra.…”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…The few studies available have addressed gene expression changes in Mn-treated cells of human (Sengupta et al 2007) or rodent origin (Baek et al 2004;HaMai et al 2006). In a genome-wide study on cultured human astrocytes (Sengupta et al 2007), Mn-induced expression changes were noted in genes involved in inflammation (upregulated), DNA replication, and repair (downregulated).…”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…A particular study which assessed in vitro cytogenetic effects of exposure to lowvibration regimes failed to detect an increase in SCE frequency in peripheral blood lymphocytes [4][5][6] . Occupational exposure to whole-body vibration and low frequency noise may have genotoxic effects in humans expressed as an increase in sister chromatid exchange levels in lymphocytes.…”
mentioning
confidence: 99%